5 Weeks of Sunshine . . . Every Day! - General Aniline & Film Corporation (Inc. Time, 1950)
Color advertisement for the General Aniline & Film Corporation describing their fadeometer testing program. A fadeometer is an accelerated aging testing device that measures the colorfastness of a material - in this case, textiles, paper, or plastics - by exposing it to a high intensity of light to determine its resistance to fading. A matter of hours in a fadeometer approximates the effect of a much longer period of ordinary daylight.
Keywords: Colorfastness (Textiles)--Testing; Colorfastness (Textiles); Photochemistry; Light; Color; Scientists, Black; African American scientists